Is emission intensity or output U-shaped in the strictness of environmental policy? - Dijkstra, Bouwe R.; Gil-Moltó, Maria J. (Wiley, 2017)
We show that, in a range of market conditions, an ever stricter environmental policy does not always lead to ever cleaner production methods and ever lower production of polluting goods. We consider an integrated technology, where firms can reduce their emission intensities in a continuous fashion. Analogous to the previous literature we find that firms' emission intensities can be U-shaped in the strictness of policy, but we show that this applies only under low profitability conditions. Under high profitability conditions, output levels are U-shaped in the strictness of the policy. The latter result is new in the literature. In the case where the U-shape arises in emission intensities, the minimum is reached where the marginal abatement cost curves intersect.